Technologie informacyjne w przedsiębiorstwie - korzyści i zagrożenia - Mroczko, Franciszek; Stańkowska, Maria (Information Technology in an Enterprises - Advantages and Threats, 2006)
The aim of the report is to present the reader with the essential conditions on which optimum exploitation together with the management of the information systems are set within the realisation of the processes taking place in enterprises. Defining the place and the role of the information systems, as well as the presentation of the sorts of management information systems are especially taken under consideration. The ways of prevailing over the competition, with the use of IT based on the value added chain theory, are presented. IT Governance, shown as a collection of processes, structures and the rules of management thanks to which IT supports the realisation of the enterprise's purposes and strategies, is also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 337-344